A MILP approach of optimal design of a sustainable combined dairy and biodiesel supply chain using dairy waste scum generated from dairy production. (October 2022) - Ivanov, Boyan; Nikolova, Desislava; Kirilova, Elisaveta; Vladova, Rayka
Highlights: MILP approach for design of a combined dairy and biodiesel supply chain. Dairy waste scum generated from dairy production used for biodiesel production. Modeling environmental and economic impact of combined supply chain. Implementing the optimization approach on a real case study from Bulgaria. Production of dairy products and dairy waste scum leads to the largest GHG emissions. Abstract: The present study proposes a mixed integer linear programming (MILP) approach for optimal design of a sustainable combined supply chain for the production of biodiesel using as a feedstock dairy waste scum generated from the implementation of optimal product portfolio of dairy supply chain. The latter includes models of economic and environmental impacts of the combined supply, constraints and an optimization criterion in terms of capital and operation costs. Тhe environmental impact is assessed through greenhouse gas emissions obtained through whole life cycle of the products. The proposed approach is implemented on a real case study from Bulgaria. As a result, optimal operating conditions of the considered supply chain, which includes: dairy farms portfolios, dairy plants portfolios, production capacity and location of biorefineries that should be built, performance of biorefineries and transportation routes are obtained. It can be used as a tool for decision-making. Graphical abstract: Image, graphical abstract